(2x+7)(2x-7)=1

Simple and best practice solution for (2x+7)(2x-7)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+7)(2x-7)=1 equation:


Simplifying
(2x + 7)(2x + -7) = 1

Reorder the terms:
(7 + 2x)(2x + -7) = 1

Reorder the terms:
(7 + 2x)(-7 + 2x) = 1

Multiply (7 + 2x) * (-7 + 2x)
(7(-7 + 2x) + 2x * (-7 + 2x)) = 1
((-7 * 7 + 2x * 7) + 2x * (-7 + 2x)) = 1
((-49 + 14x) + 2x * (-7 + 2x)) = 1
(-49 + 14x + (-7 * 2x + 2x * 2x)) = 1
(-49 + 14x + (-14x + 4x2)) = 1

Combine like terms: 14x + -14x = 0
(-49 + 0 + 4x2) = 1
(-49 + 4x2) = 1

Solving
-49 + 4x2 = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 4x2 = 1 + 49

Combine like terms: -49 + 49 = 0
0 + 4x2 = 1 + 49
4x2 = 1 + 49

Combine like terms: 1 + 49 = 50
4x2 = 50

Divide each side by '4'.
x2 = 12.5

Simplifying
x2 = 12.5

Take the square root of each side:
x = {-3.535533906, 3.535533906}

See similar equations:

| 186000x=68600x | | 5x-3=-3x+45 | | 18+2x=-10-2x | | 11x-4=4x+52 | | a^4-4a^3*b+b^2= | | 3-(x-4)=7-x | | 6-(-5b)=5b-3 | | 60-10m=-18m-4 | | 3(x+2)-2(2x-4)=38 | | 25+7=10s-7 | | 6x+12=4x+45 | | y-(y*.10)=12000 | | 12x-6=8+6x | | -r+2=20+5r | | 6v+8=-4-v | | 40a+56b= | | w^2-12w+17=0 | | 3(2g-5)=4g+13 | | r^2-5r^2+r=0 | | x+(x+12)=84 | | x-(x*.10)=12000 | | 12x-6=9y | | -t+10=-50+5t | | -t+19=-50+5t | | 8x-3=87-x | | 0.5t=-65 | | x+(x*.10)=12000 | | -5x=4 | | x*.10=12000 | | (3x+2y)(5x-4y)=0 | | -80+14x=-100-6x | | -93-9x=121-31x |

Equations solver categories